Проблема представления материнства в русской литературе XIX века - Бержайте, Дагне (SlavVaria, 2022)
Towards the Problem of Motherhood in Russian Literature of the 19th Century. For the objective reasons, Russian masculine literature of the 19th century did not pay attention to maternal subjects, which play an important role in women's prose, especially in the modern one. There is an opinion that the images of mothers depicted by the Russian writers are characterized by a tendency to self-sacrifice, and maternal love seemed to be described as exclusively iconic. This article aims to deny this statement because it’s not based on the historical development of the concept of motherhood. The examples from the works of Nekrasov, Tolstoy and Dostoevsky, who portrayed images of mothers, demonstrate that their attitude towards motherhood was based on the understanding of its functions typical to that time. The Russian writers also outlined some trends that would be put forward by feminist criticism in the field of motherhood problems.